Mexico’s Strong and Sustained Private Growth: What Is Government’s Role? - Arenas, Jorge; Levy, Daniel C. (International Higher Education, 2018)
Mexican private higher education (PHE) enrollment now approaches one million students, though government's role in this increase is complex. This article explores drivers of growth and associated government policy (or lack thereof).